Jeremy Bentham and Australia Convicts, utility and empire - Causer, Tim; Finn, Margot; Schofield, Philip (UCL Press, 2022)
Jeremy Bentham and Australia is a collection of scholarship inspired by Bentham's writings on Australia. These writings are available for the first time in authoritative form in Panopticon versus New South Wales and other writings on Australia, a volume in The Collected Works of Jeremy Bentham published by UCL Press. In the present collection, a distinguished group of authors reflect on Bentham's Australian writings, making original contributions to existing debates and setting agendas for future ones. In the first part of the collection, the works are placed in their historical contexts, while the second part provides a critical assessment of the historical accuracy and plausibility of Bentham's arguments against transportation from the British Isles. In the third part, attention turns to Bentham's claim that New South Wales had been illegally founded and to the imperial and colonial constitutional ramifications of that claim. Here, authors also discuss Bentham's work of 1831 in which he supports the establishment of a free colony on the southern coast of Australia. In the final part, authors shed light on the history of Bentham's panopticon penitentiary scheme, his views on the punishment and reform of criminals and what role, if any, religion had to play in that regard, and discuss apparently panopticon-inspired institutions built in the Australian colonies. This collection will appeal to readers interested in Bentham's life and thought, the history of transportation from the British Isles, and of British penal policy more generally, colonial and imperial history, Indigenous history, legal and constitutional history, and religious history.